Kerjasama Indonesia dan Belanda dalam Pembangunan dan Pengelolaan Infrastruktur Pelabuhan Periode 2015-2020 - Goldy Melina Febry Fajriani; Shanti Darmastuti; Sindy Yulia Putri (Jurnal Ilmiah Wahana Pendidikan, 2022)
Indonesia is one of the largest maritime countries in the world, therefore ports are very important for Indonesia in the national maritime sector. To maximize the quality of national ports to support export and import activities, international standard ports are needed. Unfortunately, ports in Indonesia still do not meet international standards, therefore Indonesia cooperates with the Netherlands as a form of Indonesia's commitment to improve the quality of national ports. Indonesia and the Netherlands established a Maritime Cooperation which was signed in Den Haag as a Memorandum of Understanding on 22 April 2016. At the implementation stage of this cooperation, several obstacles were encountered which resulted in the construction of this port being still unfinished. This study try to explain the cooperation between Indonesia and the Netherlands in the development and management of Indonesia's national port infrastructure, namely the Kuala Tanjung Port in the 2015-2020 period. This study uses a functional bilateral cooperation approach to see the economic improvement and investment of the two countries in port development in Indonesia. The results of the study show that the Indonesia-Netherlands bilateral cooperation in the construction of the Kuala Tanjung Port can be realized although in some cases it is still experiencing obstacles and is in the negotiation stage from both parties.